Dielectric Characterization and Optimization of Wide-band, Cavity-Backed Spiral Antennas - Rahman, Nahid; Sharma, Anjali; Afsar, Mohammed; Palreddy, Sandeep; Cheung, Rudolf (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a novel approach to facilitate the design of wideband, cavity-backed spiral antennas. Using this approach, first, a 2-18 GHz, two-arm cavity backed Archimedean spiral antenna has been designed in FEKO. A multilayer dielectric absorber has been introduced in the cavity to facilitate unidirectional operation of the antenna. In order to incorporate the frequencydependent complex permittivity data of the absorbing materials inserted in the cavity, precise microwave instrumentation has been used to determine these parameters experimentally. Based on this data, a genetic algorithm optimization procedure has been applied to derive the most favorable geometry of the absorbing cavity. Our results show that a design thus optimized significantly improves key performance parameters, maximizes the co-polarized gain, and minimizes the cross-polarized gain of the antenna across its operational bandwidth. We have then extended the approach to the design of a zigzagged 2-arm Archimedean spiral antenna and also a 1.5:1 ratio elliptical spiral antenna and presented the radiation characteristics here.